Faculty Job Satisfaction in District and Tehsil Colleges in India: A Comparative Review - Rana, Arzoo (Future Science, 2025)
This review examines faculty job satisfaction in Indian district and tehsil colleges, revealing significant disparities between these institutions. District colleges offer better infrastructure, salaries, and professional opportunities, resulting in higher faculty satisfaction. Tehsil colleges face challenges including poor facilities, professional isolation, and limited career advancement, leading to lower satisfaction levels. These differences reflect broader urban-rural inequalities in Indian society. The review analyzes factors affecting satisfaction including working conditions, administrative support, and work-life balance. Using sociological perspectives and Social Space theory, it demonstrates that satisfaction is shaped by structural forces beyond individual control. The study recommends policy interventions including salary parity, infrastructure improvement, democratized professional development, and administrative reforms. It emphasizes that improving faculty satisfaction is essential for educational quality and equity. The review calls for systemic changes that recognize and support faculty in all institutional contexts, particularly those serving marginalized communities in rural areas.